The Impact of Physical Activity on Mental Health of Children and Adolescents: A Comprehensive Review of Current Research and Clinical Implications - Świda, Michał; Bazarewicz, Jakub; Kubuj, Cezary; Adaśko, Grzegorz; Mazur, Urszula; Siwik, Marcin; Dmowski, Daniel; Michalska, Anna Teresa; Ogonowska, Paulina; Waszak, Julia (Quality in Sport, 2025)
Background Mental health disorders in children and adolescents, such as anxiety, depression, and ADHD, affect nearly 20% of this population and present major challenges to families, healthcare, and society [21, 29]. Standard treatments – psychotherapy and pharmacotherapy – while effective, face barriers like access, cost, side effects, and stigma [20, 24]. This has led to growing interest in alternatives, with physical activity (PA) recognized for its accessibility and mental health benefits. Aim This article reviews studies from 2018–2024 on the effects of physical activity on mental health in youth. It explores biological, psychological, and social mechanisms and considers implications for prevention and treatment strategies. Material and Methods A literature review was conducted using PubMed, Google Scholar, and Web of Science. Studies included systematic reviews, meta-analyses, RCTs, and high-quality observational research published between 2018–2024. Thirty key sources were selected. Results Evidence shows regular PA improves mental health in children and adolescents by reducing depression and anxiety, enhancing cognition and emotional regulation, and alleviating ADHD symptoms [1, 3, 4, 6, 8]. Biological mechanisms include increased BDNF, neurotransmitter modulation, reduced inflammation, and improved neuroplasticity [17, 14, 26]. PA also supports psychosocial well-being through improved self-esteem, peer relations, and coping skills. Effectiveness varies by activity type, intensity, age, gender, and psychosocial factors [25, 23, 28]. Conclusions PA is a cost-effective and accessible tool for improving youth mental health. Integrating it into clinical, educational, and community settings can aid in prevention and treatment. Future research should focus on personalized approaches, mechanisms, and digital tools for wider application.